NOTES ON DIET COMPOSITION OF FIVE SPECIES OF THE FAMILY SCINCIDAE (REPTILIA: SQUAMATA) FROM NAM DONG RARE AND PRECIOUS GYMNOSPERMS CONSERVATION AREA, THANH HOA PROVINCE - Thi Khanh Linh, Luong; Quang Vinh, Luu (Journal of Forestry Science and Technology, 2021)
We conducted the stomach content analyses of 15 specimens in five species of the Scincidae family. These examined species were collected in Nam Dong rare and precious gymnosperms conservation area, Thanh Hoa Province. The analyzed stomach contents of one specimen of Grass Sun Skink Eutropis macularius (Blyth, 1853), three specimens of Reeves’ Smooth Skink Scincella reevesii (Gray, 1838), three specimens of Forest Skink Sphenomorphus cryptotis Darevsky, Orlov & Ho, 2004, five specimens of Himalayan Forest Skink Sphenomorphus indicus (Gray, 1853) and three specimens of Hainan water skink Tropidophorus hainanus (Smith,1923) revealed in total 71 prey items. Almost stomachs of the 15 examined specimens were full of prey items, except in the stomach of three specimens of Hainan water skink Tropidophorus hainanus. There were very little prey items in T. hainanus, compared to the other skink species. Most preys were ticks, followed by spiders, woodlice, cockchafer and ants. Some materials like sand, bit of stone, plant fragments were excluded from the analysis. Among the five examined species, we found the highest prey taxon diversity for Grass Sun Skink Eutropis macularius, the lowest prey taxon diversity for Himalayan Forest Skink Tropidophorus hainanus and Reeves’ Smooth Skink Scincella reevesii. It is very likely that the prey taxon diversity was correlated with the different sample sizes of the skinks.